2014
DOI: 10.1002/cbdv.201300253
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Secondary Metabolites, Biological Activity and Glandular Trichomes of Stachys tymphaeaHausskn. from the Monti Sibillini National Park (Central Apennines, Italy)

Abstract: Stachys tymphaea (Lamiaceae) is a perennial herb growing in forest openings and dry meadows of central and southern Italy. It was investigated for the first time here, determining the content of secondary metabolites, the micromorphology of glandular trichomes, the histochemical localization of secretion, and the biological activity of the volatile oil, namely, the cytotoxic, antioxidant, and antimicrobial properties. The plant showed a peculiar molecular pattern, being rich of biophenolic compounds as flavono… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…Compounds 1, 2, 3, 4 and 5 had been already evidenced in this species (Scarpati et al 1965;Scarpati & Esposito 1967a, 1967b, Guiso et al 1974 and their presence was also confirmed in this study. Actually, these compounds and in particular harpagide (3) and its acetyl derivative (4) are considered chemotaxonomic markers for this genus and also for other related genera in the Lamiaceae family such as Ajuga (Assaad & Lahloub 1988;Breschi et al 1992), Stachys (Kotsos et al 2001;Munoz et al 2001;Háznagy-Radnai et al 2006;Venditti et al 2013aVenditti et al , 2013cVenditti et al , 2014 and Galeopsis (Wieffering & Fikenscher 1974;Venditti et al 2013b). Moreover, their occurrence may substantiate the traditional use of the plant as an anti-inflammatory agent (Guarrera 2005).…”
Section: Resultsmentioning
confidence: 94%
“…Compounds 1, 2, 3, 4 and 5 had been already evidenced in this species (Scarpati et al 1965;Scarpati & Esposito 1967a, 1967b, Guiso et al 1974 and their presence was also confirmed in this study. Actually, these compounds and in particular harpagide (3) and its acetyl derivative (4) are considered chemotaxonomic markers for this genus and also for other related genera in the Lamiaceae family such as Ajuga (Assaad & Lahloub 1988;Breschi et al 1992), Stachys (Kotsos et al 2001;Munoz et al 2001;Háznagy-Radnai et al 2006;Venditti et al 2013aVenditti et al , 2013cVenditti et al , 2014 and Galeopsis (Wieffering & Fikenscher 1974;Venditti et al 2013b). Moreover, their occurrence may substantiate the traditional use of the plant as an anti-inflammatory agent (Guarrera 2005).…”
Section: Resultsmentioning
confidence: 94%
“…The presence of a hydroxyl moiety on a hydrocarbon skeleton causes that the compound easily oxidizes and shows antioxidant properties; therefore, the possibility that the higher radical scavenging activity by the essential oil of leaves would be due to the presence of higher amount of phytol in leaves (12.08%) could not be excluded. Previous investigations demonstrated that phytol, as a natural linear diterpene alcohol, showed antioxidant activity in different assays 36,37 as well as it is utilized in manufactoring synthetic vitamins E and K. 38 The general toxicity of essential oils was assessed by brine shrimp lethality test which represent a quick, inexpensive and efficient method for evaluating extracts and essential oils toxicity and most of the time correlates fairly well with anti-proliferative and antitumor activities. 34,35 In this assay, compared with the positive control (Podophyllotoxin, LD 50 = 2.69 ± 0.30 µg/ml) , the essential oils of flowers and leaves showed potent toxicity against brine shrimps with LD 50 values of 2.25 ± 0.60 and 11.00 ± 5.19 µg/ml, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Chlorogenic acid (8) has been isolated for the first time from S. alopecuros subsp divulsa , although it has been already found in several Stachys species as S. tymphaea [8], S. lanata [30], S. officinalis [31], S. recta [32], S. byzantina , S. iberica subsp. iberica var.…”
Section: Discussionmentioning
confidence: 99%
“…The eluting system was a mixture of n -BuOH/H 2 O (82:18 v/v). From this chromatographic separation (Scheme 1) 11 compounds were isolated and identified by comparison with data reported in literature and/or by comparison with pure compounds available in our laboratory: Verbascoside (10, 12.4 mg) [14] from the assembly of fractions 8-15; stachysoside A (11, 11.2 mg) [8,15] in mixture with verbascoside (1:2) in the assembly of fractions 17-24; b-arbutin (9, 3.2 mg) [16] from the assembly of fractions 30-32; reptoside (6) [17] and 6-O-acetyl-ajugol (7) [18] in mixture in ratio 1:1.5 (25.0 mg) from the assembly of fractions 43-45; ajugoside (1, 113.7 mg) [17,19] as pure compound from the assembly of fractions 53-54; 8-O-acetyl-harpagide (2, 1.0 g) [20] from the assembly of fractions 70-88; chlorogenic acid (8) [21] in mixture with 8-O-acetyl-harpagide (2) in ratio 1:2 (109.4 mg) from the assembly of fractions 95-112; harpagide (3) [22] and chlorogenic acid (8) in mixture 3:1 (48.3 mg) from the assembly of fractions 118-122; allobetonicoside (4) and chlorogenic acid (8) in mixture 10:1 (29.1 mg) from the assembly of fractions 133-135; allobetonicoside (4, 100.7 mg) [23] as a pure compound from the assembly of fractions 144-163; 4¢-O-galactopyranosyl-teuhircoside (5) [6] in mixture with allobetonicoside (4) in ratio 3:1 (24.7 mg) from the assembly of fractions 166-169.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation